Knockout of Epstein-Barr Virus BPLF1 Retards B-Cell Transformation and Lymphoma Formation in Humanized Mice - Whitehurst, Christopher B.; Li, Guangming; Montgomery, Stephanie A.; Montgomery, Nathan D.; Su, Lishan; Pagano, Joseph S. (mBio, 2015)
BPLF1 of Epstein-Barr virus (EBV) is classified as a late lytic cycle protein but is also found in the viral tegument, suggesting its potential involvement at both initial and late stages of viral infection. BPLF1 possesses both deubiquitinating and deneddylating activity located in its N-terminal domain and is involved in processes that affect viral infectivity, viral DNA replication, DNA repair, and immune evasion. A recently constructed EBV BPLF1-knockout (KO) virus was used in conjunction with a humanized mouse model that can be infected with EBV, enabling the first characterization of BPLF1 function in vivo . Results demonstrate that the BPLF1-knockout virus is approximately 90% less infectious than wild-type (WT) virus. Transformation of human B cells, a hallmark of EBV infection, was delayed and reduced with BPLF1-knockout virus. Humanized mice infected with EBV BPLF1-knockout virus showed less weight loss and survived longer than mice infected with equivalent infectious units of WT virus. Additionally, splenic tumors formed in 100% of mice infected with WT EBV but in only 25% of mice infected with BPLF1-KO virus. Morphological features of spleens containing tumors were similar to those in EBV-induced posttransplant lymphoproliferative disease (PTLD) and were almost identical to cases seen in human diffuse large B-cell lymphoma. The presence of EBV genomes was detected in all mice that developed tumors. The results implicate BPLF1 in human B-cell transformation and tumor formation in humanized mice. IMPORTANCE Epstein-Barr virus infects approximately 90% of the world's population and is the causative agent of infectious mononucleosis. EBV also causes aggressive lymphomas in individuals with acquired and innate immune disorders and is strongly associated with diffuse large B-cell lymphomas, classical Hodgkin lymphoma, Burkitt lymphoma, and nasopharyngeal carcinoma (NPC). Typically, EBV initially infects epithelial cells in the oropharynx, followed by a lifelong persistent latent infection in B-cells, which may develop into lymphomas in immunocompromised individuals. This work is the first of its kind in evaluating the effects of EBV's BPLF1 in terms of pathogenesis and lymphomagenesis in humanized mice and implicates BPLF1 in B-cell transformation and tumor development. Currently, there is no efficacious treatment for EBV, and therapeutic targeting of BPLF1 may lead to a new path to treatment for immunocompromised individuals or transplant recipients infected with EBV. Epstein-Barr virus infects approximately 90% of the world's population and is the causative agent of infectious mononucleosis. EBV also causes aggressive lymphomas in individuals with acquired and innate immune disorders and is strongly associated with diffuse large B-cell lymphomas, classical Hodgkin lymphoma, Burkitt lymphoma, and nasopharyngeal carcinoma (NPC). Typically, EBV initially infects epithelial cells in the oropharynx, followed by a lifelong persistent latent infection in B-cells, which may develop into lymphomas in immunocompromised individuals. This work is the first of its kind in evaluating the effects of EBV's BPLF1 in terms of pathogenesis and lymphomagenesis in humanized mice and implicates BPLF1 in B-cell transformation and tumor development. Currently, there is no efficacious treatment for EBV, and therapeutic targeting of BPLF1 may lead to a new path to treatment for immunocompromised individuals or transplant recipients infected with EBV.